Analysis of epidemiological trends in chronic diseases of Chinese residents. Issue 4 (29th November 2020) - Shilian, Hu; Jing, Wang; Cui, Cheng; Xinchun, Wu
Abstract : Following the population aging in China, dramatic changes have been observed in the spectrum of diseases among Chinese residents. E.g., the incidence and prevalence of chronic diseases, such as cardiovascular, cerebrovascular, metabolic, and respiratory diseases, are constantly growing. Additionally, osteoporosis, sarcopenia, and chronic renal disease have gradually become common chronic diseases among the elderly. Chronic diseases in the elderly have ranked first in the spectrum of diseases among Chinese residents. Therefore, understanding the trends of main chronic diseases among Chinese residents and developing proactive countermeasures have become a major public health issue for China.